Investigation and Assessment of the Influence of Cascaded Hydropower Plants on Fish Resources in the Qiuxiangjiang River - LIU Jie; CHEN Lan; CUI Ke; ZHANG Lijuan; LIU Xieting; LI Xin; HU Guocheng (Renmin Zhujiang)
The development of cascaded hydropower plants in middle and small rivers has a significant impact on fish resources,mainly includes the destruction of fish habitat.The Qiuxiangjiang River belongs to the first-class tributary of the Dongjiang River in Guangdong Province.This paper evaluates the present situation of fish resources in the Qiuxiangjiang River by aquatic ecosystem investigation and sampling analysis,and compares it with historical data.The results show that due to cascade hydropower development and other human activities in the Qiuxiangjiang River Basin,the suitable habitat for fish decreases.The species and numbers of fish decrease sharply compared with historical records.The fish population structure is relatively unstable,and the fish diversity also gradually reduces.Therefore,for the cascade hydropower development in middle and small rivers,attention should be paid to overall planning the entire river basin,protecting the integrity of the river's aquatic ecosystem,and strictly requiring hydropower plants to build discharge facilities and strengthen supervision of their operation.